Environmental and Religious Character in Silat Tapak Suci in Students' Perspective - Bahagia Bahagia; Rimun Wibowo; Leny Muniroh; Abdul Karim Halim; Irfan Maulana; Irma Nur Safitri (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to find moral, social and religious values as well as the environment in silat tapak suci. The research method used is descriptive qualitative. The selection of research subjects with purposive sampling technique. Data was collected using in-dept interview, observation and documentation techniques. The results showed that members are conducted some behaviour such as ablution activities, prayers, short lectures or cults, reading Al-Fatihah letters, and closing prayers and there was another advisory activity at the end of the silat practice. Another finding is that players are not allowed to hit sensitive parts such as the neck, but are allowed to hit the waist, both the right and left and the chest to the stomach. Even if the opponent has fallen then it cannot be hit. At the same time there is a natural environment value because when there is a level up test, members will be brought camping close to nature both in forest areas and river banks. Silat is also healthy because using the right moves will expend energy and be healthy for the heart, lungs and other body parts.